Use of the kidney injury molecule-1 as a biomarker for early detection of renal tubular dysfunction in a population chronically exposed to cadmium in the environment - Werawan Ruangyuttikarn (2018)
Cadmium (Cd) has been found as an environmental pollutant in Mae Sot district, Tak province, Thailand. Prolong exposure to high levels of Cd of the resident increases high risk of Cd toxicity especially to kidney which is the primary target of Cd. In order to investigate the early effect of Cd induced renal dysfunction, a kidney injury molecule-1 (KIM-1), a novel biomarker of renal tubular dysfunction, was measured using an enzyme linked immunosorbent assay (ELISA). The method was validated and used to quantify the KIM-1 concentrations in the urine of 700 subjects (260 men, 440 women) who lived in the Cd contaminated area. The KIM-1 concentrations were compared to the concentrations of two conventional renal tubular dysfunction biomarkers, N-acetyl-β-D-glucosaminidase (NAG) and β 2 -microglobulin (β 2 -MG). Urinary KIM-1 was correlated with urinary and blood Cd as well as NAG. After adjustment of age and smoking, urinary KIM-1 was correlated with blood Cd more than urinary NAG did. Clear dose response relationships of urinary KIM-1 with urinary Cd were shown in both men and women. These results indicate that the urinary KIM-1 might be more sensitive biomarker than urinary NAG and β 2 -MG for an early detection of renal tubular dysfunction. It is useful as a tool to detect renal effect of toxicity due to chronic Cd exposure at high level. © 2013 Ruangyuttikarn et al.